THE IMPACT OF EMPLOYEE INVOLVEMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE - Sharma, Heena; Venkateswaran, C. (International Journal of Psychosocial Rehabilitation, 2020)
–It has been largely believed that the individuals are the foremost resource of any organization and the fundamental element for attaining exceptional performance. Studies directed to examine the organizational- level influence of the Employee Involvement (EI) initiatives has become common in the contemporary phenomenon. The literature incorporates the researches directed on investigating the performance impact of individual Employee Involvement practices, such as participative-decision making, training, performance-based rewards, and information sharing practices, as well as the research directed to investigate the impact of systems of Involvement initiatives on the establishment outcomes.Researchers from diverse domains have proposed varied empirical and theoretical frameworks for establishing the association among the EI practices and the organizational outcomes. While the review of every one of these frameworks is outside the scope of this research, the earlier literature broadly unites on the significance of Employee Involvement practices in ascertainment of organizational and employee outcomes. Based on this fundamental, our study focussed on determining the relationship of EI in problem-solving and decision-making with the organizational performance. The study utilized structural equation modelling to examine the impact of EI on performance. The results of our study are not supportive of the assertion that synergies or complementarities between the EI practices would be related positively with the performance of an organization, contrary to the hypothesis formulated in the study. The study also highlighted some key limitations and observations which deserve attention.